Dholuo Kincepts in Western Kenya - Washington Onyango-Ouma (LibraryPress@UF, 2020)
The Luo are a Nilotic people living in western Kenya, north-eastern Tanzania and in western Uganda. Their language, Dholuo, forms part of the Western Nilotic group of languages. This article presents the traditional kincepts (kinship terminology) of the Luo people as described by elders living in Central Sakwa location, Siaya County, western part of Kenya. The kincepts for consanguine as well as affine relatives in up to three ascending and five descending generations are described. The paper applies a combined linguistic and anthropological approach. Linguistically, the terms are analysed in relation to current Dholuo vocabulary, grammar and modes of expression. Anthropologically, the Luo kinship rules of patrilineality and virilocality are considered. The domain of kincepts is a research field bringing together linguistics, anthropology and history. It contributes to the inquiry of diachronic linguistics, which can provide insights on the development and interaction of related languages as well as population groups’ migratory patterns not least in parts of the world where written historical sources are scarce.